Relation of Chatbot Usage Towards Customer Satisfaction Level in Indonesia - Andri Sahata Sitanggang; R Fenny Syafariani; Febilita Wulan Sari; Wartika Wartika; Novrini Hasti (International Journal of Advances in Data and Information Systems, 2023)
In customer service for businesses in Indonesia, chatbot are predicted to be a pillar of business, especially chatbot that are able to reach customers proactively, provide availability 24 hours a day, even fulfill requests and answer customer questions quickly which has an important value in customer satisfaction factor in use of chatbot in Indonesia. The world of chatbots is very diverse to study from various aspects such as from a technological point of view, the study of natural language conversation of chatbots done by Shawar and Atwell concluded that chatbots are useful as a “tool”, entertainment tools, also learning and practice tools, as well as tools to help with e-commerce and other fields. Another chatbot study compared the ability of offline customer service agents in general on marketing and how to represent an online business with a chatbot and its effect on improving relationships with customers. In conclusion, chatbots provide an efficient alternative solution to conventional customer service in reducing the repetitive tasks of human admins in solving customer problems, or allowing the ability to respond to various customer needs.